Efficiency evaluation of Neem (Azadirachta indica) oil and copper-ethanolamine in the protection of wood against a subterranean termite attack - Mbitnkeu Fetnga Tchebe, Tatiana (Les (Ljubljana), 2020)
The demand for environmentally safe preservatives for wood is increasing all around the world. This study is focused on the evaluation of the ability of Neem (Azadirachta indica) seed oil and copper-ethanolamine to protect Sydney blue gum (Eucalyptus saligna) and Ayous (Triplochiton scleroxylon) against termites. Wood blocks were impreg-nated with solutions of Neem oil in acetone and/or an aqueous solution of copper-ethanolamine. Impregnated woods with a retention rate ofup to 108.3 kg/m3 were obtained. A leaching experiment was used to determine the fixation of preservatives in wood. The termicidial effect of the preservatives was studied through exposure in a termitarium. Neem oil was less efficient for Sydney blue gum but showed significant protection for Ayous at a higher retention rate. At the concentration investigated, the treatment of both wood species with copper-ethanolamine solution was not suitable. However, a combination of copper-ethanolamine and Neem oil showed an improvement in the protection of Sydney blue gum wood. Nevertheless, the impregnated woods still suffered an increased termite attack after leaching.
Keywords: baker; copper; etanolamin; ethanolamine; izpiranje; leaching; les; neem oil; nimovo olje; preservation; termite; termiti; wood; zaščita